2018
DOI: 10.1111/papt.12202
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about feeling: Using trait emotional intelligence in understanding the associations between early maladaptive schemas and coping styles

Abstract: Objectives Maladaptive interpersonal schemas can trigger distressing emotions and drive dysfunctional behaviour that leads to difficulties in interpersonal relationships and perpetuates the original maladaptive schemas. This study sought to identify patterns of association between trait emotional intelligence (TEI), early maladaptive schemas (EMS), and coping styles in a non‐clinical sample. Emotionality profiles were hypothesized to be associated with EMS severity and poorer coping, as early experiences can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 55 publications
3
22
0
1
Order By: Relevance
“…They extend previously found relations between modes and temperamental traits (Lobbestael et al, 2010) and Big-Five trait factors (Jacobs et al, 2020). They also add to prior evidence that low global TEI is a common feature of personality pathology (e.g., Ke & Barlas, 2020;Krajniak et al, 2018;Martskvishvili & Mestvirishvili, 2014;Petrides, P erez-Gonz alez, et al, 2007;Sinclair & Feigenbaum, 2012). Criterion A of DSM-5's AMPD (APA, 2013) defines personality malfunction in terms of impaired self-functioning and interpersonal functioning.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…They extend previously found relations between modes and temperamental traits (Lobbestael et al, 2010) and Big-Five trait factors (Jacobs et al, 2020). They also add to prior evidence that low global TEI is a common feature of personality pathology (e.g., Ke & Barlas, 2020;Krajniak et al, 2018;Martskvishvili & Mestvirishvili, 2014;Petrides, P erez-Gonz alez, et al, 2007;Sinclair & Feigenbaum, 2012). Criterion A of DSM-5's AMPD (APA, 2013) defines personality malfunction in terms of impaired self-functioning and interpersonal functioning.…”
Section: Discussionsupporting
confidence: 78%
“…Schemas can thus be regarded as characteristic adaptations to personality traits (cf. McAdams & Pals, 2006), which is consistent with conceptually coherent correlations between TEI and schema scores (Ke & Barlas, 2020) and irrational emotional beliefs (Petrides, G omez & P erez-Gonz alez, 2017). The general manifestation frequency of modes may thus reflect characteristic adaptations to traits as well.…”
Section: Introductionsupporting
confidence: 72%
“…In a study directed by Lazarus and Folkman [ 11 ]; Pelletier [ 63 ] observed that family members of organ donors felt several different emotions and utilized different coping strategies. Ke and Barlas [ 64 ] investigated the relationship between trait emotional intelligence, early maladaptive schemas, and coping styles and they observed that lower levels of trait emotional intelligence were linked with a higher possibility for maladaptive coping in response to early maladaptive schemas. Consistent with the above discussion, the following hypothesis is offered: EI is significantly related to coping strategies, and each EI dimension (self-emotion appraisal, other-emotion appraisal, regulation of emotion, use of emotion) has a different effect on coping strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, a low level of TEI is significantly associated with anxiety, anger, disruptive behaviors, and with both internalizing and externalizing symptoms [16]. In contrast, Mavroveli and colleagues [17] have found that adolescents with a high level of TEI are generally less predisposed to developing depressive or somatic symptoms, and are more likely to successfully cope with difficult events [18]. Moreover, previous research has found that people with high TEI show a positive attitude towards stressful events, namely resilience [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%